Marx dans un nouveau cadre welfariste - Pelletier, Gérard (L'Actualité économique)

(untitled) (HEC Montréal, 1979)
Samuelson's statement about Marx being a minor post-Ricardian from the viewpoint of pure economic theory leaves one perplexed. Is theoretical welfare economics a part of pure economic theory? This paper shows that theoretical welfare economics is the foundation of the theory of economic policy and intervention. Marx also sets forth a theory of intervention based on economic arguments. Therefore, Marx should be studied within the broader scope of theoretical welfare economics. Moreover, Marx's system contains not only analytical devices but also important value judgments and the theory of welfare economics aims to study the interrelations between value judgments and economic interventions. Methodological contradictions are shown in, and removed from, the theory of welfare economics in order to show the framework of Marx's entire system. The system as a whole is far beyond the realm of Ricardian economics, for it can be consistent and scientific although it contains value judgments. Samuelson's narrow approach and fuzziness in the methodological foundations of welfare economics hindered an appreciation of the full value of Marx's approach.